Does Graft type affect the Cost of Anterior Cruciate Ligament Reconstruction: A Time-Driven Activity-Based Costing Approach Comparing Hamstring and Bone Patella Bone Autograft. Issue 7 (31st July 2020) - Flagstad, Ilexa; Reams, Megan; Tompkins, Marc; Nelson, Bradley; Siljander, Breana; Parikh, Harsh; Cunningham, Brian
Objectives: Annually, an estimated 250, 000 anterior cruciate ligament (ACL) reconstructions are performed. Operative management of ACL injuries has increased 22% between 2002 and 2014. With national healthcare expenditures rising at unsustainable rates, an improved understanding of healthcare costs is essential to identifying avenues of inefficiency and implement innovative solutions. This study is purposed to utilize time-driven activity-based costing (TDABC) to estimate the costs for the two-year care episode in the surgical reconstruction of ACL tears. Provided its high incidence, the operative reconstruction of ACL injuries serves as a prime setting for this study. Methods: This study follows 611 patients that underwent an ACL reconstruction for an acute ACL tear between 2009-2016 within a single outpatient orthopaedic surgery center (Figure 1). Patient demographics were collected via the electronic medical record (EMR) (Table 1). The total cost-of-care was determined using time-driven activity-based-costing (TDABC). This formula derives the cost of care as a function of the time spent for each activity and personnel cost contributions for all involved. This process was performed at all phases: surgical intervention, all clinical follow-ups, and physical therapy (PT) sessions. Results: A total of 611 patients were included for this investigation. The patient sample was primarily female (n=355, 58.1%) with an average age of 28.9 + 12.9 [27.9, 30.0], and average BMI of 25.5 + 4.5 [25.2, 25.9]. The majority of the patients identified with an Anesthesiologist Society of America (ASA) score of 1 (n=505, 83.9%). The average operative time was 107.1 + 31.5 minutes [104.6, 109.6]. The average TDABC cost-of-care was derived at 3364.95 + 958.99 [3288.75, 3441.14]. Surgical costs occupied the greatest proportion of the overall cost-of-care, 1836.11 (53.2%), followed by costs relating to surgical implants, 911.61 (27.1%), physical therapy appointments, 342.00 (10.2%), and clinical follow-up appointments, 318.77 (9.5%) (Figure 1). A total of 459 (75.1%) patients were treated with an autograft, averaging a total cost-of-care of 2882.19, with the 90th percentile costing 3427.23 and 10th percentile costing 2343.08, reporting a 16.0% variability in costing. Of the 152 (24.9%) allografts, the average cost of care was 4884.10, with the 90th percentile costing 5321.50 and 10th percentile costing 4411.25, reporting a 9.0% variability. Hamstring autografts reported a significantly higher cost-of-care when compared to bone-patellar-bone (BTB) autografts (Hamstring: 3120.10 vs BTB: 2718.60; p<0.01). Conclusion: Given the increasing frequency of ACL procedures performed, an improved understanding of its costing components is critical for implementing change and strategizing solutions for increasing healthcare costs. Operative costs drive the total cost of care with implants, graft choice, and surgical resources constituting almost 80% for the two-year cost episode. With the growing focus of healthcare transitioning towards value-based healthcare delivery and cost reduction, identifying areas of costing inefficiency in surgical decision-making and implant-choice provides an avenue to reduce costs. Figure 1. Table 1. Population characteristics for study sample between 2009-2016 (N=611) n (% of N) or Mean SD (95% CI) Gender Female: 355 (58.1%) Male: 256 (41.9%) Age 28.912.9 (27.9, 30.0) BMI 25.54.5 (25.2, 25.9) Anxiety 105 (17.3%) Depression 82 (13.5%) ASA 1: 505 (83.9%) 2: 92 (15.3%) 3: 5 (0.8%) Operative Time (Minutes) 107.131.5 (104.6, 109.6) Other Ligament Tear Lateral Collateral Ligament (LCL): 6 (1.0%) Medial Collateral Ligament (MCL): 30 (4.9%) Posterior Collateral Ligament (PCL): 3 (0.5%) Meniscus Tear Lateral: 213 (38.9%) Medial: 170 (31.1%) Meniscetomy 188 (40.6%) Graft Source Allograft: 151 (24.7%) Autograft: 460 (75.3%) Graft Type Bone-Patellar Tendon-Bone Graft (BTB): 400 (65.4%) Hamstring: 197 (32.2%) Posterior Tibialis: 9 (1.5%) Anterior Tibialis: 5 (0.8%) SANE @ Baseline SANE @ 1-Year SANE @ 2-Years 63.423.3 (61.5, 65.4) 88.412.7 (87.0, 89.9) 85.622.4 (83.8, 87.5) SANE 1-Year 24.122.8 (21.5, 26.7) SANE 2-Years 22.929.3 (20.4, 25.4) KOOS @ Baseline KOOS @ 1-Year KOOS @ 2-Years 65.315.9 (63.6, 66.9) 79.712.7 (77.5, 81.9) 83.213.5 (81.8, 84.6) KOOS 1-Year 17.416.1 (14.6, 20.1) KOOS 2-Years 17.916.8 (16.2, 19.7) Total Cost 3364.95958.99 (3288.75, 3441.14) 1-Year Value Coefficient () 0.550.53 (0.46, 0.64) 2-Year Value Coefficient () 0.580.57 (0.52, 0.64) A Summary of the study populations' characteristics